Polyproline fold-In imparting kinetic stability to an alkaline serine endopeptidase - Rohamare, Sonali B.; Dixit, Vaishali; Nareddy, Pavan Kumar; Sivaramakrishna, D.; Swamy, Musti J.; Gaikwad, Sushama M. (Biochimica Et Biophysica Acta-Proteins and Proteomics, 2013)
Polyproline II (PPII) fold, an unusual structural element was detected in the serine protease from Nocardiopsis sp. NCIM 5124 (NprotI) based on far UV circular dichroism spectrum, structural transitions of the enzyme in presence of GdnHCl and a distinct isodichroic point in chemical and thermal denaturation. The functional activity and conformational transitions of the enzyme were studied under various denaturing conditions. Enzymatic activity of NprotI was stable in the vicinity of GdnHCl upto 6.0 M concentration, organic solvents viz, methanol, ethanol, propanol (all 90% v/v), acetonitrile (75% v/v) and proteases such as trypsin, chymottypsin and proteinase K (NprotI:protease 10:1). NprotI seems to be a kinetically stable protease with a high energy barrier between folded and unfolded states. Also, an enhancement in the activity of the enzyme was observed in 1 M GdnHCl upto 8 h, in organic solvents (75% v/v) for 72 h and in presence of proteolytic enzymes. The polyproline fold remained unaltered or became more prominent under the above mentioned conditions. However, it diminished gradually during thermal denaturation above 60 degrees C. Thermal transition studies by differential scanning calorimetry (DSC) showed scan rate dependence as well as irreversibility of denaturation, the properties characteristic of kinetically stable proteins. This is the first report of PPII helix being the global conformation of a non structural protein, an alkaline serine protease, from a microbial source, imparting kinetic stability to the protein. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Conformation; differential scanning calorimetry; Kinetic stability; Nocardiopsis sp.; Polyproline fold; Serine protease